ACCELERATION HEALING AND OSSEO-INTEGRATION PROCESSES OF CPTI IMPLANT BY COATING TEETH WITH COLLAGEN-POLYCAPROLACTONE FIBER SCAFFOLD - Al-Bayati, Shanai; Jassim, Raghdaa; Jabur, Akram; Bazzaz, Ayoub A. (PT. Antis International Publisher, 2024)
Objective: This study aimed to enhance osseointegration and healing by combining electrospinning techniques with collagen and polycaprolactone (PCL) as a coating for commercial pure titanium (CpTi) implants. Methods: In vitro experiments utilized glacial acetic acid as a solvent system to create collagen/PCL coatings with varying PCL concentrations (10%, 15%, 20% w/v). Morphological and physical characterizations were conducted using scanning electron microscopy (SEM), atomic force microscopy (AFM), and wettability tests. In vivo studies involved implanting collagen/PCL-coated CpTi cylinders into the femoral bone of New Zealand rabbits, followed by histological analysis at 2 and 6 weeks. Results: SEM revealed that scaffolds with higher PCL concentrations exhibited finer nanofiber structures (average diameter: 232 nm) and enhanced hydrophilicity and roughness. Histological analysis demonstrated significant osteogenic activity and basal bone formation, with well-formed bone plates observed at 6 weeks for implants coated with 20% collagen and 20% PCL. Novelty: The study highlights the potential of electrospun collagen/PCL coatings to create optimal surface properties for dental implants, achieving improved tissue integration and healing outcomes. This innovative approach demonstrates the versatility of electrospinning for fabricating fibrous scaffolds that can incorporate therapeutic agents, offering transformative implications for regenerative medicine and implantology.